Effect of the educative intervention on healthful feeding in the adoption of positive nourishing habits by mothers of students, users of Clas Chinchao-Acomayo – 2011 - Llanos de Tarazona, Marina (2017)
An educative experiment was realised on healthful feeding, with the aim of demonstrating the adoption of positive nutritional habits by the usuary mothers of students of the CLAS Chinchao, Acomayo, during the 2011. The sample conformed 93 mothers, distributed in groups experimental and control, selected probabilistically, of simple random form. For the data collection we applied to a guide of interview and a card of physical evaluation. The descriptive analysis, was realised with measures of central tendency and the inferencial by means of statistical the Z of Wilcoxon, x2 of Mc Nemar, and Marginal Homogeneity, at a level of confidence to 95% and ≤ p 0.05, supported in software SPSS V20 for Windows. Significant differences were demonstrated [Z = -2,236; 0.025 p =], in the nutritional state, between groups and moments of the study, in addition in the experimental group, the changes (rank) were merely positive. When comparing, the variable frequency in the food consumption, also were significant differences [Z = 56,017; 0.000 p =] in the experimental group, whereas in the group control, were not observed such differences (p > 0,05). In the same way, there were significant differences in the experimental group and during the moments of the study [HM = -8,492; 0.000 p =], in the variable predominance of nutrients in the diet, fact that was not observed in the group control (p > 0,05). Conclusion. The educative intervention determines differences (improvement) in positive the nutritional habits of the mothers of the students in study [Z = -6,751; 0.000 p =].